Stable schemes for second-moment turbulent models for incompressible flows - Ferrand, Martin; Hérard, Jean-Marc; Norddine, Thomas; Ruget, Simon (Comptes Rendus. Mécanique)
A stable scheme is proposed in this paper in order to obtain approximate solutions of second-moment turbulent models for incompressible flows with or without thermal transport equation. The analysis of the convective terms, which includes the solution of the associated Riemann problem, enables to propose a standard projection scheme, and to get rid of spurious oscillations.